Improving Student Activities and Learning Outcomes Using the JNT Model and the Monopoly Game in Class IV SD - Fauzi, Zain Ahmad; Ihsan, Muhammad (Budapest International Research and Critics University, 2022)
Civics learning about diversity is very important to create a sense of tolerance in children, but the problems found in this research are that students are passive, students' interest in learning is low and bored quickly in learning and the lack of student mastery of PPKn content on diversity material in Indonesia. This study aims to describe teacher activities, student activities and also analyze student learning outcomes when learning Civics on the diversity of materials that exist in Indonesia in fourth grade students of SDN Sungai Rangas. The type of research used is classroom action research (CAR) which was carried out for 2 meetings, this research was carried out in grade IV SDN Sungai Rangas which consisted of 16 students. The types of data presented are teacher activity data and student activities obtained through observation, and also student learning outcomes data obtained from test results. The benchmark for success in learning completeness research is that 80% of students obtain or exceed the KKM, the specified value is 75. Based on the findings and results of this study, it can be concluded that learning activities using the JNT learning model and Monopoly Game are able to provide an increase in student activities and learning outcomes.